Compilation and implementation of a quality improvement program in a typical South African machining and assembly environment - Grib, B. J. P.(Ben Johannes Petrus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1986.